Investigating the Effect of Thermal Annealing and Changing the Concentration of GO in GO/PVA Nanocomposites on Their Structural, Electrical, and Optical Properties - Lala Gahramanli; Mustafa Muradov; Goncha Eyvazova; Mahammad Baghir Baghirov; Sevinj Mammadyarova; Gunel Aliyeva; Elman Hajiyev; Faig Mammadov; Stefano Bellucci (ChemEngineering, 2023)
The present research involves producing graphene oxide (GO) using the Hummers method, generating a composite using GO and PVA, and analyzing these composites’ structural and optical characteristics. PVA and GO were used in varied percentages to deal with the issue of how the features of GO/PVA alter depending on concentration. The impact of thermal annealing on the structure and optical characteristics of GO/PVA materials at various concentrations were also investigated. UV-VIS was used to investigate the band gap value of GO/PVA composites. The band gap value changed due to an increase in the concentration of GO in the composites in the PVA and the impact of thermal annealing. The band gap value, specific resistance, and dielectric constant were all found to be well controlled by varying the thermal annealing temperature and the concentration of GO in this case. Differential Scanning Calorimetry (DSC) and thermogravimetric analysis (TGA) were performed on pure PVA and GO/PVA samples in various percentages of GO in order to examine the effect of temperature on the physical properties of (n = 1, 2, 3, 5, 20%) nGO%/PVA nanocomposites. Thermal stability increased as the fraction of GO in the PVA polymer matrix increased.